Assessing employer satisfaction: An attempt to enhance graduate employability at an institution of higher learning - Brits, H.J. (South African Journal of Higher Education, 2019)
This article discusses the concept employability or graduateness within the context of the South African higher education environment. It reflects on a satisfaction survey that was conducted at a university of technology in order to evaluate the perspective and satisfaction of the graduates’ employers. This aligns with the institution’s quality management philosophy that is underpinned by the notion of customer satisfaction. The survey measured the employers’ satisfaction as well as their perspectives on the importance of attributes that are required from graduates in the workplace. The article argues that institutions should develop strategies to embed key skills in the curricula and recommends continuous reviews to evaluate the successful implementation of these strategies to enhance employability.